Evaluasi Kesesuaian Rekonstitusi Sediaan Steril di Bangsal Anak RS Universitas Sebelas Maret - Ayu Cahyani Abidin; Hidayah Apriliawan; Niken Luthfiyanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Reconstitution of injectable drugs involved mixing sterile drug powders with appropriate sterile solvents prior to parenteral administration. This critical pharmacy practice was particularly vital in pediatrics where dosing errors and contamination posed significant risks. Reconstitution errors could lead to chemical instability, therapeutic failure, and serious adverse effects including toxicity or nosocomial infections. This study aimed to evaluate the appropriateness of sterile injectable drug reconstitution procedures in the Pediatric Ward of Universitas Sebelas Maret Hospital across five parameters: dosage calculation, solvent selection, solvent volume, post-reconstitution storage temperature, and Beyond Use Date (BUD) assignment. A descriptive observational study with prospective design was conducted among pediatric inpatients from December 2025 to January 2026. Seventy cases of pediatric injectable drug administrations were sampled using saturated (total) sampling technique. Primary data were collected through direct pharmacist reconstitution observations while secondary data came from medical records and sterile preparation worksheets. Compliance was benchmarked against gold standards: Pediatric Injectable Drugs 10th edition and Handbook on Injectable Drugs 17th edition. Perfect compliance (100%) was achieved for dosage, solvent selection (NaCl 0.9%, sterile water), and reconstitution volumes. However, storage temperature compliance (2-8°C for light-sensitive drugs) was only 68%, while BUD documentation aligned with post-reconstitution stability in 70% of cases, leaving 2% critical non-compliance posing patient safety risks. While reconstitution technical execution was excellent, cold chain monitoring and BUD documentation required systemic improvements through regular training, real-time temperature tracking, and stricter Standard Operating Procedures to ensure pediatric pharmacotherapy safety.